2008
DOI: 10.2174/138161208784480117
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Evaluation of Adenosine A2A Receptors as Potentially “Druggable” Targets in Huntingtons Disease

Abstract: Huntington's disease (HD) is a dominantly inherited neurodegenerative disorder caused by the expansion of a polymorphic CAG trinucleotide repeat encoding a poly-glutamine tract within the Huntingtin protein. GABAergic enkephalin neurons of the basal ganglia, which show the highest levels of expression of adenosine A(2A) receptors, are the most vulnerable in HD. Such a selective neuronal vulnerability, which occurs despite ubiquitous expression of mutant and normal Huntingtin, has suggested that adenosine A(2A)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 60 publications
(32 citation statements)
references
References 171 publications
(249 reference statements)
1
29
1
1
Order By: Relevance
“…Consistent with the possible beneficial role of the A 2A R in HD, Mievis and colleagues demonstrated that elimination of the A 2A R exacerbated HD progression in a mouse model of HD (55). Future investigations are required to evaluate the therapeutic potential of A 2A R drugs (56).…”
Section: Figmentioning
confidence: 89%
“…Consistent with the possible beneficial role of the A 2A R in HD, Mievis and colleagues demonstrated that elimination of the A 2A R exacerbated HD progression in a mouse model of HD (55). Future investigations are required to evaluate the therapeutic potential of A 2A R drugs (56).…”
Section: Figmentioning
confidence: 89%
“…The neuroprotective effect of A 2A R activation in these injury models has been primarily attributed to inhibition of inflammatory processes and vascular effects. Furthermore, the neuroprotective effects of A 2A R agonists and antagonists are dependent on the stages of pathological processes (Li et al, 2006;Popoli et al, 2008), extents of brain injury (Blum et al, 2003), or routes of drug delivery (Jones et al, 1998a).…”
Section: Introductionmentioning
confidence: 99%
“…In this platform, expression of mHTT exon 1 fragment (73 CAG) reduced striatal and cortical neuron survival compared with normal Q-length controls. Screening in 96-well plate format led to identification of several compound classes with known and novel neuroprotective actions, including compounds that had been previously identified in screens using different endpoints (e.g., the ROCK inhibitor Y-27632) [25] or acted on gene targets implicated in other HD models (e.g., inhibitor of kappa B (IÎșB) kinase and the adenosine 2A receptor) [58][59][60].…”
Section: Target-based and Phenotypic Screening Using High-content Anamentioning
confidence: 99%